Multidimensional Poverty: Identification of Deprivation Characteristics of Papua's Population Poverty in 2020 - Dedy Susanto; Titis Setya Wulandari (Department of Urban and Regional Planning, Universitas Diponegoro, 2021)
Papua is a growing province with rich potential yet has the highest rate of poverty and lowest rank of HDI in Indonesia. As poverty has been measured limited on monetary alone, anti-poverty programs and policies have become limited. Although the first goal of the SDGs clearly states that poverty is a multidimensional problem. Thus, measuring multidimensional poverty in Papua is needed. This study uses a multidimensional poverty formulation (MPI) with the 2019 Seychelles framework compiled by OPHI and the Seychelles National Bureau of Statistics in four dimensions: Decent Living Standards, Health, Education, and Employment. Considering data availability, not all indicators are available in the March 2020 SUSENAS data, so a four-dimensional approach in 13 indicators is carried out to calculate multidimensional poverty in Papua.As a result, the percentage of Papuans who experienced multidimensional poverty (H) was 71.2 percent, with the intensity (A) as 47.3 percent. The results show 0.337 points in MPI (M0), meaning that the average deprivation experienced by all residents in Papua Province is 33.7 percent of the 13 indicators from MPI. The dimensions with the most significant contribution are health (0.301), then employment (0.266), education (0.258), and a decent standard of living (0.175). Based on area classification, there is an imbalance between the contribution of multidimensional poverty at urban and rural levels with 0.220 and 0.780.This study found that Papuans experienced multidimensional poverty, the most deprived in the health dimension and indicators of school completion at least SMA or equivalent.